POESIA SUDANESE. Museum Combonianum, No. 12, by LIVIO TESCAROLI. Editrice Nigrizia, Bologna, 1961. pp. 117. - Jones, A. M. (International Library of African Music, 1961)
pages: 107
Keywords: Poetry; African Music; Sudan